Impact of marijuana on venous thromboembolic events: Cannabinoids cause clots in trauma patients. Issue 1 (July 2020) - Stupinski, Jack; Bible, Letitia; Asmar, Samer; Chehab, Mohamad; Douglas, Molly; Ditillo, Michael; Gries, Lynn; Khurrum, Muhammad; Joseph, Bellal
Abstract : BACKGROUND: Tetrahydrocannabinoids (THC) can modulate the coagulation cascade resulting in hypercoagulability. However, the clinical relevance of these findings has not been investigated. The aim of our study was to evaluate the impact of preinjury marijuana exposure on thromboembolic complications (TEC) in trauma patients. METHODS: We performed a 2-year (2015–2016) analysis of American College of Surgeons Trauma Quality and Improvement Program database and included all adult (≥18 year) trauma patients. Patients were stratified based on preinjury exposure to Marijuana: THC + ve and THC −ve groups. We performed propensity score matching to control for confounding variables: demographics, comorbidities, injury parameters, hospital course, and thromboprophylaxis use. Outcomes were TEC (deep venous thrombosis, pulmonary embolism, stroke, myocardial infarction) and mortality. RESULTS: Of 593, 818 trauma patients, 678 patients were matched (THC + ve: 226 vs. THC −ve: 452). Mean age was 34 ± 15 years, Injury Severity Score was 14 (10–21). There was no difference between the two groups regarding age ( p = 0.75), sex ( p = 0.99), Injury Severity Score ( p = 0.54), spine Abbreviated Injury Scale (AIS) ( p = 0.61), head AIS ( p = 0.32 ), extremities AIS ( p = 0.38), use of unfractionated heparin ( p = 0.54), use of low molecular weight heparin ( p = 0.54 ), and hospital length of stay ( p = 0.87). Overall, the rate of TEC was 4.3% and mortality was 4%. Patients in THC + ve group had higher rates of TEC compared with those in THC −ve group (3.5% vs. 1.1%, p = 0.03). The rate of deep venous thrombosis (6.6% vs. 1.8%, p = 0.02) and PE (2.2% vs. 0.2%, p = 0.04) was higher in THC + ve group. However, there was no difference regarding the rate of stroke ( p = 0.24), myocardial infarction ( p = 0.35) and mortality ( p = 0.28). CONCLUSION: THC exposure increases the risk of TEC in patients with trauma. Early identification and treatment for TEC is required to improve outcomes in this high-risk subset of trauma patients. LEVEL OF EVIDENCE: Prognostic study, level III. Abstract : Supplemental digital content is available in the text.